The Antidepressant Effect of Chlorella vulgaris on Female Wistar Rats (Rattus norvegicus Berkenhout, 1769) with Chronic Unpredictable Mild Stress Treatment - Gisella Intan Soetantyo; Mulyati Sarto (Universitas Gadjah Mada, 2019)
Depression is a disabling mental disorder, predicted to become the world's number 2 disability by 2020 by the World Health Organization (WHO, 2018). Chronic stress is one of the triggers for depression, causing an imbalance in brain chemicals and antioxidants levels. Although antidepressant is a common treatment, discomforting side effects has compromised its efficacy, prompting the search for alternative medicines. Chlorella vulgaris is a microalgae famous for its excellent protein and antioxidant content. In this study, C. vulgaris (360 mg/kg p.o.) potency of antidepressant in chronic unpredictable mild stress (CUMS) model of depression in female rats was evaluated compared to amitriptyline (2,25 mg/kg p.o.) for 14 days. Two types of C. vulgaris namely cultivation sourced and commercially-sold, were used. Sucrose preference test, forced swim test (FST) and open field test (OFT) were used as depression-like behaviour test to validate C. vulgaris effect. Adrenal glands were observed to further understand its effect on the stress organ. The CUMS method produced rats with depressive-like behaviour evidently by reduced body weight, sucrose preference, exploring behaviour in OFT, and increased immobility duration in FST. Furthermore, an increase in adrenal weight, fasciculata zone, and reticularis zone was observed. Both C. vulgaris significantly (p<0,05) reversed depressive-like behaviour in rats subjected to CUMS, but not the size of adrenal glands. This finding indicated both types of C. vulgaris has the potential to be an alternative antidepressant but because of the short duration of treatment, it’s speculated that C. vulgaris may not have exhibited enough difference structurally yet.